Critical needs for research in veterinary science (National Academies Press, 2005)
Research in veterinary science is critical for the health and well-being of animals, including humans. Food safety, emerging infectious diseases, the development of new therapies, and the possibility of bioterrorism are examples of issues addressed by veterinary science that have an impact on both human and animal health. However, there is a lack of scientists engaged in veterinary research. Too few veterinarians pursue research careers, and there is a shortage of facilities and funding for conducting research. This report identifies questions and issues that veterinary research can help to address, and discusses the scientific expertise and infrastructure needed to meet the most critical research needs. The report finds that there is an urgent need to provide adequate resources for investigators, training programs, and facilities involved in veterinary research.